Energy Pathways for Future Norwegian Residential Building Areas - Natasa Nord; Yiyu Ding; Ola Skrautvol; Stian Fossmo Eliassen (Energies, 2021)
Owing to stricter building energy requirements, future buildings will be characterized by low base loads and occasional high peaks. However, future building areas will still contain existing and historical buildings with high energy demand. Meanwhile, there is a requirement that future building areas should obtain energy from renewable energy sources, while existing buildings need to be transited to renewables. Therefore, the aim of this study was to develop an approach for modelling energy pathways for future Norwegian residential building areas by analyzing different energy supply systems. Several calculation methods were combined: building simulation, energy supply technology simulation, heat demand aggregation, and data post-processing. The results showed that the energy pathways would be very dependent on CO2-factors for energy sources, and it is hard to predict accurate CO2-factors. An increasing housing stock development would slightly increase the CO2 emissions towards 2050, although the new buildings used much less energy and the existing buildings underwent renovation. A constant housing stock would yield a 22–27% reduction of CO2 emissions by 2050. This showed that implementing stricter building codes had a lower impact on the total CO2 emissions than CO2-factors and energy technologies. The focus should lie on energy supply systems.